(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
This is a case study for the development of a poly(ethylene glycol) diacrylate-based hydrogel for an additive manufacturing process. By introducing a photoinitiator and an UV absorber into the poly(ethylene glycol) diacrylate a spatially and temporally three-dimensional polymerization takes place. To demonstrate the possible printing resolution a scaffold is generated on a modified commercial stereolithography system.